Learners Through Understanding Gestalt Learning Theory: Classroom Implementation Experience Individual-Based Approach - Manurung Paisal (Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2019)
The purpose of this paper is to provide information to educators on one theory of learning andteaching there. The theory in question is the Gestalt theory. This theory has been implemented inthe learning process is at the University of Asahan in English Education Study Program in CourseIntroduction to English Literature at half V. The methodology used is descriptive methodquantitative research with an individual approach experience approach. The results of the dataquantitative approach this method is described as a result of the application of learning theoryGestalt. The results of this quantitative descriptive explaining that the new students realize thatlearning theory is petrified educators in understanding all aspects of the students, but the physicaland psychological aspects as a self-understanding reach an average value of 33.78 or equal meaningthat an understanding of learners achieving 80% based on the scale of reference benchmark. Thus,in theory, this is a very important part for educators to convey information to students as a learningprocess to improve the cognitive, affective and psychomotor.